(untitled) (Comprehensive Journal of Science, 2025)
The aim of this study was to identify the reality of e-learning and its role in enhancing the quality of the educational process from the perspective of a number of faculty members at the College of Arts and Sciences, Misurata. The researcher employed the descriptive–correlational method to address the main research question: What is the current status of e-learning and its role in improving the educational process, based on the responses of selected faculty members to the designated questionnaire? The study sample consisted of 50 faculty members. The findings revealed that the level of e-learning use among the participants was moderate. The sample also indicated the presence of significant obstacles that substantially hinder the effective implementation of e-learning.